Implementación de control diversor de carga automático para microcentral hidroeléctrica - Rojas-Durán, Jhonny (Instituto Tecnológico de Costa Rica, 2018)
The present graduation project report was developed in the SME Interdinámica Energía, a Costa Rican company dedicated to the development of projects with renewable energies. The aim of the project was to implement an automatic load diversifier controller for the control of battery charge states in small hydroelectric plants. The installations of hydroelectric power plants without connection to the electric network require the use of a battery bank, as an energy storage element, and a charge controller. These controllers are safety systems for the turbine, as it keeps the plant operating under nominal conditions, maximizing system performance in general and extending the life of the equipment. The charge controllers available on the market are expensive and often have difficulty adapting to the characteristics of the installation. The project consists of the implementation of an automatic load diversifier controller, capable of varying up to 2kW of power for battery banks with nominal voltage of 12V and 24V.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, 2018
Keywords: Pyme; Recursos renovables; Controladores; Carga; Microcentrales hidroeléctricas; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics